Lupus Masquerading as a Drug Reaction in HIV Infection - Anisa Mosam; Koraisha Hoosen; Ncoza C. Dlova (MDPI AG, 2019)
An HIV-positive female on antiretroviral therapy (ART) presented with an annular eruption diagnosed as a drug reaction based on histology of a lichenoid dermatitis. She responded to oral steroid therapy and discontinuation, but progressed to develop features in keeping with cutaneous lupus. Although the antinuclear factor remained negative, her low serum complement levels, histology, and clinical features pointed to a diagnosis of subacute lupus in the setting of HIV infection. She responded well to antimalarial therapy and recommenced ART.